1995
DOI: 10.1002/path.1711750106
|View full text |Cite
|
Sign up to set email alerts
|

mdm2 gene alterations and mdm2 protein expression in breast carcinomas

Abstract: This study investigates the mdm2 gene status and expression in 66 surgically resected human breast carcinomas, with correlations with clinico-pathological and biological data (histological type, grading, steroid receptor status, p53 expression, proliferative activity). Four (7.7 per cent) out of 52 informative cases bear mdm2 gene amplification (four-to ten-fold) and 8 (15.4 per cent) of 52 cases showed borderline amplification (three-fold). Nine (13.6 per cent) out of 66 cases showed strong mdm2 nuclear immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 13 publications
4
78
0
Order By: Relevance
“…In the specific case of breast cancer, which may well be a suitable target for such interventions, we have previously demonstrated that elevated levels of Hdm2 protein in proliferating cultures of breast cancer cell lines with ER␣ ϩve , compared with ER␣ Ϫve , phenotypes, correlates with transcription from the P2 promoter of the hdm2 gene in the ER␣ ϩve cells (37). In breast tumor samples, Hdm2 protein is overexpressed compared with normal cells in as many as 50% of cases (34 -36); however, in most cases in which Hdm2 expression is observed in breast cancer, it is limited to small patches of cells in the tumor (34). Additionally, one study determined that, of the tumors in which hdm2 mRNA was up-regulated, only 69% showed Hdm2 protein overexpression (35).…”
Section: Discussionmentioning
confidence: 99%
“…In the specific case of breast cancer, which may well be a suitable target for such interventions, we have previously demonstrated that elevated levels of Hdm2 protein in proliferating cultures of breast cancer cell lines with ER␣ ϩve , compared with ER␣ Ϫve , phenotypes, correlates with transcription from the P2 promoter of the hdm2 gene in the ER␣ ϩve cells (37). In breast tumor samples, Hdm2 protein is overexpressed compared with normal cells in as many as 50% of cases (34 -36); however, in most cases in which Hdm2 expression is observed in breast cancer, it is limited to small patches of cells in the tumor (34). Additionally, one study determined that, of the tumors in which hdm2 mRNA was up-regulated, only 69% showed Hdm2 protein overexpression (35).…”
Section: Discussionmentioning
confidence: 99%
“…Over 10 years ago, it was first noted that MDM2 mRNA and protein levels are heightened in breast tumors that express the estrogen receptor (ER), a critical component of the estrogen signaling pathway (Sheikh et al, 1993;Gudas et al, 1995;Marchetti et al, 1995;Okumura et al, 2002). Subsequently, the expression of ER-a was shown to induce transcription of MDM2.…”
Section: Gender and The Estrogen Signaling Pathwaymentioning
confidence: 99%
“…From this clone a 400 bp I/I fragment of exon II was used for hybridization. The MDM2 probe was a 585 bp reverse transcription PCR (RT-PCR) fragment spanning nucleotides 650-1214 of the published cDNA sequence (Oliner et al, 1992;Marchetti et al, 1995). The  and  probes were kindly provided by Dr Theillet (Adnane et al, 1991).…”
Section: Hybridizationmentioning
confidence: 99%